KAJIAN EKONOMI PENGUSAHAAN HUTAN SAGU DI PROPINSI RIAU (Economics study of sago forest utilization in Riau Province) - O K Karyono; Hariyanto Dwiprabowo; Boen M Purnama (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Besides being used as raw material for food industries sago flour has also been know as a staple food in riau province. The utilization of sago for industrial input as well as for staple food will encourage the development of agro based industry wich in turn would lead to the improvement of sago farmer’s income.Based on this study,cost of sago plantation, harvesting and transportation of sago stem to the processing plant was Rp 1.074.500,- per ha absolute margin received by farmer amounted Rp. 119.187,50 per ha per year (rotation period was 8 years)Average processing costs of converting saho stem to sago flour amounted to Rp. 256.685,- per ton (wet sago flour) so that absolute margin received by sago processing plant in average was Rp. 134.315,- per ton, while the selling price at factory in Cirebon was Rp. 425.000,- per ton sago flour.Benefit cost ratid analysi show that net benefit cost ratio 1.33 and gross benefit cost ratio 1.44 and profitability ratio 1.61 show that further development of sago utilization in riau provice is economically feasible.